From Decolonization to Ethnonationalism: A study of Malaysia’s School History Syllabuses and Textbooks 1905 - 2020 - Wan Ali Wan Mamat; Abdul Rahman Ali (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2022)
The history syllabus and textbooks in the Malaya/Malaysia education system became a matter of interest only within the few years before the country’s independence in 1957 to eventually become a controversy among concerned educationists and academicians. During the British colonial period, the syllabus and textbooks, despite being European-centric/English oriented and far from being Malayan in form and content, were generally accepted without much dispute, perhaps because during this period the number of local historians and educated elites were still small. Education in the country was then under the colonial dominance. Furthermore, history teachers, having been educated under the British colonial system, even after some years of independence were more familiar and at ease with the old colonial curriculum. However, after Malaya (later Malaysia) gained Independence from the British in 1957 and Malaysia in 1963, the controversy about the right approach in the teaching of Malayan history came to the fore. The main contentious issue about the history curriculum was Malayanization and Malaysia-centric versus Euro-centric syllabus.